A MODELLING STUDY OF VERTICAL SURFACE DISPLACEMENTS AT CONVERGENT PLATE MARGINS - Buiter S.J.H.; Govers R.; Wortel M.J.R. (My University, 2001)
During the evolution of a subduction zone system, variations are likely to occur in, for example, surface plate velocities and buoyancy of the subducting lithosphere. We quantify vertical surface displacements at convergent plate margins resulting from such imposed variations. For this purpose we use a 2-D numerical model in which the lithospheric plates have an effective elastic thickness. We first define a model in which the subducting plate is driven by its negative buoyancy and a velocity at its surface side boundary. Its equilibrium topography (after around 2 Myr) is the reference level for examination of surface displacements resulting from variations in buoyancy, velocity of the surface plates, friction along the interplate contact and subduction zone roll-back. We find that a decrease (increase) in buoyancy of the subducting material leads to a deepening (uplift) of the plate margins. An increase in friction along the subduction fault deepens the overriding plate margin. Subduction zone roll-back due to sinking of the negatively buoyant subducting plate induces subsidence of the overriding plate margin. This subsidence is reduced when roll-back takes place in a land-locked basin setting. Trench retreat forced by the motion of the overriding plate is characterized by higher topography of the overriding plate margin than the case of retreat due to the sinking of the negatively buoyant slab. In the first case in-plane stress in the back-arc region is compressive while it is tensional for roll-back due to the sinking of the slab. We conclude that vertical surface displacements during ongoing subduction may reach a magnitude of a few kilometres on the overriding and subducting plate margins.
Keywords: ACTIVE MARGIN; FINITE ELEMENT METHOD; SUBDUCTION; SUBSIDENCE; UPLIFT